1983
DOI: 10.1002/j.1460-2075.1983.tb01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation of histone H1O in CHO cells: a flow cytofluorimetric study after double staining of the cells.

Abstract: The regulation of histone H1O content throughout the cell cycle of non‐synchronized Chinese hamster ovary (CHO) cells has been studied using double fluorescent staining and flow cytofluorometry. In exponentially growing cells, the amount of H1O was found to be proportional to the DNA content of the cells, indicating that the protein is synthesized throughout the cell cycle. However, when cells were arrested in G1 at saturation density the amount of H1O was greater than that found in G1 cells of the exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Role of the cell cycle in the regulation of the H 1°m RNA In contrast to the main type histones, the synthesis of HI0 is not linked to the S phase of the cell cycle but rather is synthesized throughout the cell cycle (Chabanas et al, 1983). Experiments with inhibitors of DNA synthesis, on the other hand, showed that the experimental induction of H 10 synthesis occurs in those cells which are in the late S or G2 phases (Chabanas et al, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Role of the cell cycle in the regulation of the H 1°m RNA In contrast to the main type histones, the synthesis of HI0 is not linked to the S phase of the cell cycle but rather is synthesized throughout the cell cycle (Chabanas et al, 1983). Experiments with inhibitors of DNA synthesis, on the other hand, showed that the experimental induction of H 10 synthesis occurs in those cells which are in the late S or G2 phases (Chabanas et al, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known that foreign as well as host‐cell protein production can be dependent on the cell‐cycle phase (Kubbies and Stockinger, 1990) and that several native genes are synthesized at increased rates in the G1 phase (Buell and Fahey, 1969; Garatun‐Tjeldsto et al, 1976; Chabanas et al, 1983; Chafouleas et al, 1984; Herz et al, 1991; Gu et al, 1993). This phenomenon was thus used to optimize the productivity of commercially relevant cell lines such as hybridoma and CHO cells by prolonging or blocking cells at the G1 phase (Suzuki and Ollis, 1990; Al‐Rubeai et al, 1992; Jenkins and Hovey, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…When effects on HeLa cells of treatment with butyrate or dimethylsulfoxide, serum withdrawal or density inhibition are compared, each shows an increase in the Hl"/H1 ratio, but for a given cell line this ratio depends on the method used to block the cells from dividing [26,27,451, and the amount of H1" differs among the cell lines compared. We show here that neither butyrate, which inhibits cell proliferation in GI [8,141, nor TPA, which was chosen as a substance that causes metabolic changes in HepG2 cells [28], affect HI" mRNA levels. Thus, our data indicate that the H1" inRNA level in HepG2 cells is constitutively maintained at an elevated level and cannot be further increased.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate, which was used as a potential inducer of HI" expression in HepG2, causes a drastic increase in H1" protein concentration in a variety of systems [8,9,13,321. As described by Chabanas et al [9] for murine melanoma cells, butyrate induction takes place in the late S or G, phase of the cell cycle, and the cells, which are blocked in G I , accumulate high levels of H1" protein.…”
Section: Discussionmentioning
confidence: 99%